Pengabdian Kepada Masyarakat Pembuatan Jembatan Di Kampung Stamplat Dusun Ciparay, Desa Indragiri, Kecamatan Rancabali, Kabupaten Bandung - Daud R. Wiyono; Yosafat Aji Pranata; Deni Setiawan (Universitas Batanghari Jambi, 2023)
Stamplat Village is part of Ciparay Hamlet, Indragiri Village, Rancabali District, Bandung Regency. Indragiri Village is located in a mountainous area with an area of 2642.16 hectares and is located at an altitude of 1400–1700 meters above sea level, and has a topography that varies from gently sloping, hilly and steep. In the middle of Stamplat Village there is a water channel with a large enough discharge both during the rainy season and dry season, because the water comes from springs in the hills in the area. Traffic passes through waterways using bridge infrastructure, but the existing bridge does not allow medium-sized vehicles to pass so that residents' activities are disrupted due to inadequate bridge capacity. Stamplat Village has the potential for local materials, namely river stone material used for the existing bridge which can be reused if the bridge is repaired. Stamplat Village has potential resources (especially adult men) who have the ability to carry out the construction and repair of public facilities, in this case the repair of a bridge that is 3.6 m wide and 3 m long. Repair of the bridge using WF200x100 steel beams with beam spacing of 1 m with reinforced concrete slabs 17 cm thick, capable of carrying an even load of 3500 kg/m2. The foundation and the retaining wall behind the bridge are made of stone, while the repair of the water canal uses gabions made of sandbags.